Versatile Functions of Somatostatin and Somatostatin Receptors in the Gastrointestinal System - Shamsi, Bilal Haider; Chatoo, Mahanand; Xu, Xiao Kang; Xu, Xun; Chen, Xue Qun (Frontiers in Endocrinology, 2021)
Somatostatin (SST) and somatostatin receptors (SSTRs) play an important role in the brain and gastrointestinal (GI) system. SST is produced in various organs and cells, and the inhibitory function of somatostatin-containing cells is involved in a range of physiological functions and pathological modifications. The GI system is the largest endocrine organ for digestion and absorption, SST-endocrine cells and neurons in the GI system are a critical effecter to maintain homeostasis via SSTRs 1-5 and co-receptors, while SST-SSTRs are involved in chemo-sensory, mucus, and hormone secretion, motility, inflammation response, itch, and pain via the autocrine, paracrine, endocrine, and exoendocrine pathways. It is also a power inhibitor for tumor cell proliferation, severe inflammation, and post-operation complications, and is a first-line anti-cancer drug in clinical practice. This mini review focuses on the current function of producing SST endocrine cells and local neurons SST-SSTRs in the GI system, discusses new development prognostic markers, phosphate-specific antibodies, and molecular imaging emerging in diagnostics and therapy, and summarizes the mechanism of the SST family in basic research and clinical practice. Understanding of endocrines and neuroendocrines in SST-SSTRs in GI will provide an insight into advanced medicine in basic and clinical research.